Higher Education in Brazil and the policies for increasing the number of vacancies from Reuni: advances and controversies - Maria Célia Borges (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
This paper presents a discussion on the policies to expand Higher Education, stating the influences of neoliberalism and explaining the contradictions in legislation and reforms at this level of education in Brazil after the 1990s. It questions the model of the New University with regard to the Brazilian reality and the poor investments available for such a reform. It calls attention to the danger of prioritizing the increase in the number of vacancies instead of the quality of teaching, something which would represent the scrapping of the public university. It highlights the contradictions of Reuni, with improvised actions and conditioning of funds, through the achievement of goals. On one hand, it recognizes the increasing number of vacancies in Higher Education and, on the other, it reaffirms that democratization of access requires universities with financial autonomy, well-structured courses with innovative curricula, qualified professors, adequate infrastructure, and high quality teaching, with research aiming the production of new knowledge, as well as university extension.